Evaluation of a Direct Ion Storage dosimeter efficiency to measure dose during interventional cardiology procedures - Bergman Nelson Sanchez Munoz; Carla Daruich de Souza; Silvio Ricardo Pires; Adriano Henrique Pereira Barbosa; Regina Bitelli Medeiros (Brazilian Journal of Radiation Sciences)
Intracardiac electrophysiological invasive procedures guided by fluoroscopy aim to study the cardiac depolarization process. Depending on the complexity of the clinical case, both patients and professionals are subjected to radiation for a prolonged period. This work evaluated if a direct ions storage (DIS) dosimeter could measure occupational doses in different regions of the physician's body during these procedures. Doses were monitored close to the left eye (LE), right eye (RE), extremity (left ankle), and thorax, as well as the environmental dose, positioning the dosimeter in the center of the equipment gantry. These doses were evaluated in 31 procedures using 01 DIS dosimeter in each region. The Mann-Whitney U test demonstrated that the values obtained in the different regions represent different samples, while the Spearman test demonstrated that there is no evidence that there is a correlation between the data recorded in the different regions. DIS was effective in recording the doses in the LE region and the doses of dispersed radiation (Arc), with the values obtained: (30 quartile / maximum): LE (0.07 / 0.20 mSv); Arc (0.38 / 1.53 mSv). It was not possible to compare occupational doses between different regions of the physician's body, limiting its use as a complementary monitor in the control of occupational doses.